Prevalencia de hábitos deformantes y anomalías dentomaxilofaciales en niños de 3 a 6 años de edad, 2002-2003 Prevalence of deforming habits and dentomaxillofacial anomalies in 3-6 years-old children, 2000- 2003 (Editorial Ciencias Médicas, 2004)
A descriptive cross-sectional study was performed on 576 children aged 3-6 years from 5 day care centers cared for by "Ormani Arenado" dental clinic located in Pinar del Río province from September 2002 to September 2003. It was aimed at defining the prevalence of deforming habits and dentomaxillofacial anomalies. These children were examined according to variables such as sex, age, existing deforming habits, and classification of occlusion and dentomaxillofacial anomalies. It was found that less than half of the children presented with malocclusion, the linking between deforming habits and dentomaxillofacial anomalies was very significant, abnormal deglutition and digit sucking were the most frequent deforming habits and that the most observed dentomaxillofacial anomalies were anterior open bite and dentoalveolar prognathism. It was concluded that there is a close association of deforming habits and dentomaxillofacial anomalies.